2012
DOI: 10.1007/s13402-012-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter methylation of the RASSF1A and APC genes in epithelial ovarian carcinoma development

Abstract: The observed aberrant methylation frequencies of the RASSF1A and APC gene promoters indicate that an accumulation of epigenetic events at these specific TSG promoters may be associated with the malignant transformation of benign cystadenomas and LMP tumours to carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…RASSF1A acts as a tumor suppressor gene in the RAS pathway and can regulate proliferation, induce apoptosis, and bind to and stabilize microtubules . Previous studies showed that the frequency of promoter hypermethylation of RASSF1A in ovarian carcinomas was 40-58% (Yoon et al, 2001;Bhagat et al, 2012). In our study, epithelial ovarian cancers exhibited RASSF1A gene promoter methylation frequencies of 48.6% (17/35).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…RASSF1A acts as a tumor suppressor gene in the RAS pathway and can regulate proliferation, induce apoptosis, and bind to and stabilize microtubules . Previous studies showed that the frequency of promoter hypermethylation of RASSF1A in ovarian carcinomas was 40-58% (Yoon et al, 2001;Bhagat et al, 2012). In our study, epithelial ovarian cancers exhibited RASSF1A gene promoter methylation frequencies of 48.6% (17/35).…”
Section: Discussionsupporting
confidence: 57%
“…Ibanez de Caceres et al (2004) reported a significant correlation between methylation status, tumor grade, CA125 levels, and stage in ovarian cancer. However, we found that the methylation status of RASSF1A was not related to age, grade, stage, histological type, ascites, and CA125, which was similar to the results of Bhagat et al (2012). Homeodomain-containing genes encode transcriptional factors that function during embryonic development to control patterning, differentiation, and proliferation (Gorski and Walsh, 2003).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Methylation of the RASSF1A promoter is described as an early and frequent event in tumorigenesis, thus RASSF1A can serve as a useful diagnostic marker in cancer screening (Dammann et al, 2000;Dammann et al, 2001;Liu WJ et al, 2013), including ovarian cancer (Agathanggelous et al, 2001;Yoon et al, 2001;Rathi et al, 2002;Ibanez et al, 2004;Makarla et al, 2005;Choi et al, 2006;Ma et al, 2009;BonDurant et al, 2011;Bhagat et al, 2012).…”
Section: Aberrant Methylation Of Rassf2a In Tumors and Plasma Of Patimentioning
confidence: 99%